Assessment of the quality of life of moderate and severe burn patients in Saudi Arabia using the Burn Specific Health Scale-Brief - Ali M. Alkhathami; Salah Aldekhayel (Elsevier, 2024)
Improvements in the mortality rate for burn injuries has led to an increase in the number of major burn survivors. Burn injuries pose significant physical and psychological consequences that impact the quality of life of burn survivors. The current study assessed the quality of life of major burn survivors in Saudi Arabia using the Burn Specific Health Scale-Brief (Arabic version). A total of 48 major burn survivors completed a validated online survey. Additional data, including demographics, burn injury characteristics, and treatment strategies, were collected from electronic health records. The mean extent of the patients' burn injuries was 32 % of total body surface area. The average number of surgical interventions was four (ranging between two to 15 procedures). Over 40 % of the patients experience significant difficulties in performing their jobs. About 94 % are bothered by the appearance of their burn scars. Exposure to sun and hot weather remains a significant burden for the majority. The mean scale score was 99 out of 148. The number of surgical interventions was found to be related to a lower quality of life score (p-value = 0.02). Gender, age, and total body surface area had no predictive value for lower quality of life after burn injury. Even several years after sustaining burn injuries, burn patients continue to exhibit long-term complications and limitations in their functional status and daily living. Furthermore, the number of surgical interventions burn survivors have undergone is a negative predictor for their quality of life.